THE ROLE OF STRESSOR-STRAIN-SATISFACTION RELATIONSHIPS: AN EMPRICAL STUDY IN NEW ZEALAND - Huat, Andy Ang; David, Nguyen (International Business Education Journal, 2010)
The current research explores the job and life attitudes among New Zealand managers. The author provides a model of stressor, strain and job satisfaction and put forward a research question. The relationship between stressors, strain and satisfaction appear to respond to a significant gap in the literature. This research has amassed one of the largest datasets on managers’ health and wellbeing in Australia. A pilot study was conducted as part of a larger questionnaire survey of self-reported 1041 participants. This study was conducted using different modes of the survey that tapped into mode preferences among the participants. A sequence of regression analysis and descriptive test produced some interesting results. This implications of the findings were discussed.